Development and Application of Lyrics of Poetry About Faith, Islam, and Ihsan to Optimize Student Character - Nur Hasyim; Darul Nurjanah; Riza Hadikusuma (International Journal Labs, 2025)
This research aims to develop and apply lyrics of poetry with the theme of Iman, Islam, and Ihsan as a medium for character learning in the university environment. This development model departs from the need for religious media that is touching, easy to remember, and in harmony with Islamic values. The method used is research and development according to Sugiyono (2019) with the stages of needs analysis, design, expert validation, and limited implementation. The results of the study show that the lyrics of the verses developed have a strong spiritual and emotional touch, helping students understand the basic concepts of Islam through aesthetic language. The application of these poems increases religious awareness, worship discipline, and social empathy of students. Thus, Islamic poetry can function as a medium for internalizing the values of faith, Islam, and ihsan in the context of character education in higher education.